Whole intestinal microbiota transplantation is more effective than fecal microbiota transplantation in reducing the susceptibility of DSS-induced germ-free mice colitis - Yang, Yapeng; He, Jinhui; Wang, Yuqing; Liang, Lifeng; Zhang, Zeyue; Tan, Xiang; Tao, Shiyu; Wu, Zhifeng; Dong, Miaomiao; Zheng, Jixia; Zhang, Hang; Feng, Shuaifei; et al. (Frontiers in Immunology, 2023)
Fecal microbiota transplantation (FMT) is an emerging and effective therapy for the treatment of inflammatory bowel disease (IBD). Previous studies have reported that compared with FMT, whole intestinal microbiota transplantation (WIMT) can more precisely replicate the community structure and reduce the inflammatory response of the host. However, it remains unclear whether WIMT is more effective in alleviating IBD. To examine the efficacy of WIMT and FMT in the treatment of IBD, Germ-free BALB/c mice were pre-colonized with whole intestinal microbiota or fecal microbiota before being treated with dextran sodium sulfate. As expected, the symptoms of colitis were alleviated by both WIMT and FMT, as demonstrated by the prevention of body weight loss and decreased the Disease activity index and histological scores. However, WIMT's anti-inflammatory effect was superior to that of FMT. In addition, the inflammatory markers myeloperoxidase and eosinophil peroxidase were dramatically downregulated by WIMT and FMT. Furthermore, the use of two donors facilitated the regulation of cytokine homeostasis in colitis mice; the level of the pro-inflammatory cytokine IL-1β in the WIMT group was significantly lower than that in the FMT group, while the level of the IL-10 was significantly higher than that in the FMT group. Both groups showed enhanced expression of occludin to protect the intestinal barrier in comparison with the DSS group, and the WIMT group demonstrated considerably increased levels of ZO-1. The sequencing results showed that the WIMT group was highly enriched in Bifidobacterium, whereas the FMT group was significantly enriched in Lactobacillus and Ochrobactrum. Correlation analysis revealed that Bifidobacterium was negatively correlated with TNF-α, whereas Ochrobactrum was positively correlated with MPO and negatively correlated with IL-10, which might be related to different efficacies. Functional prediction using PICRUSt2 revealed that the FMT group was considerably enriched in the L-arginine biosynthesis pathway, whereas the WIMT group was enriched in the L-lysine fermentation to acetate and butanoate pathway. In conclusion, the symptoms of colitis were subsided to varying degrees by the two different types of donors, with the WIMT group being more effective than the FMT group. This study provides new information on clinical interventions for IBD.